1999
DOI: 10.1046/j.1432-1327.1999.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Entry of [(1,2‐13C2)acetyl]‐l‐carnitine in liver tricarboxylic acid cycle and lipogenesis

Abstract: The biochemical pathways involved in acetyl-l-carnitine utilization were investigated in conscious, freely moving rats by 13 C NMR spectroscopy. Following 4-h [(1,2-13 C 2 )acetyl]-l-carnitine infusion in fasted animals, the free carnitine levels in serum were increased, and an efflux of unlabelled acetyl-l-carnitine from tissues was observed. [(1,2-13 C 2 )Acetyl]-l-carnitine was found to enter biosynthetic pathways in liver, and the acetyl moiety was incorporated into both cholesterol and 3-hydroxybutyrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Increased acetyl carnitine levels in muscle and plasma have been found in obesity models or after chronic high-fat feedings (21,41). Although not directly confirmed, previous reports indicate that the products of incomplete oxidation (acetyl CoA and acetyl-carnitine) may also be directed to fatty acid biosynthesis pathways (2). In findings similar to ours in liver, Koves et al also found that exercise training increased the flux of both ␤-oxidation and TCA cycle improving the rate of complete fatty acid oxidation to CO 2 in skeletal muscle, providing evidence that exercise training can enhance the complete oxidation of lipids in both liver and skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Increased acetyl carnitine levels in muscle and plasma have been found in obesity models or after chronic high-fat feedings (21,41). Although not directly confirmed, previous reports indicate that the products of incomplete oxidation (acetyl CoA and acetyl-carnitine) may also be directed to fatty acid biosynthesis pathways (2). In findings similar to ours in liver, Koves et al also found that exercise training increased the flux of both ␤-oxidation and TCA cycle improving the rate of complete fatty acid oxidation to CO 2 in skeletal muscle, providing evidence that exercise training can enhance the complete oxidation of lipids in both liver and skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…In carnitine-supplemented animals, urinary excretion of total acylcarnitines increased 130-fold. Still, a large proportion of the circulating acylcarnitines are retained by renal reabsorption (56), implying that these molecules might be destined for other metabolic fates (57)(58)(59). Interestingly, acetylcarnitine supplements have proven therapeutically effective in models of neuronal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that carnitine supplementation increased the levels of dopamine, epinephrine, and serotonin particularly in regions rich in cholinergic neurons (Juliet et al, 2003). In a careful NMR study, the [ 13 C] label from [(1,2-[ 13 C](2))acetyl]-L L -carnitine was also found in liver glutamate, glutamine, and glutathione (Aureli et al, 1999) in accord with entry into the mitochondrial acetyl-CoA pool associated with the tricarboxylic acid cycle. In brain, after injection of [1-14 C]acetyl-L L -carnitine, 60% of the radioactivity was recovered as CO 2 consistent with energy generation.…”
Section: Therapeutic Use Of Short-chain Acyl-carnitine Estersmentioning
confidence: 95%